Multiscalar critical models with localised cubic interactions - Sabine Harribey; William H. Pannell; Andreas Stergiou (Journal of High Energy Physics)
Abstract Interface localised interactions are studied for multiscalar universality classes accessible with the perturbative ε expansion in 4 – ε dimensions. The associated beta functions at one loop and partially at two loops are derived, and a wide variety of interface conformal field theories (CFTs) is found, even in cases where the bulk universality class is free or as simple as the Wilson-Fisher description of the O(N) model. For up to three scalar fields in the bulk, interface fixed points are classified for all bulk universality classes encountered in this case. Numerical results are obtained for interface CFTs that exist for larger numbers of multiscalar fields. Our analytic and numerical results indicate the existence of a vast space of interface CFTs, much larger than the space of defect CFTs found for line and surface defect deformations of multiscalar models in 4 − ε dimensions. In this vast space, stable interfaces found for free and O(N) bulks belong to the F 4 family, with global symmetries SO(3), SU(3), Sp(6) and F 4, realised with N = 5, 8, 16, 24 scalar fields, respectively.